Analisis Jenis Konjungsi Koordinatif pada Artikel Pendidikan dan Edukasi dalam Website kelasjuara.id Edisi Oktober 2024 sebagai Bahan Ajar Siswa SMA - Ashlihatur Rosyada; Alysya Nadia Putri; Yuliana Irawati; Riska Rovita Sari; Yasfa Indi Al Ghifari; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Sugiana Sugiana (BADAN PENERBIT STIEPARI PRESS, 2025)
Conjunctions are categories that connect words with words, clauses with clauses, or sentences with sentences to paragraphs with paragraphs. Conjunctions function to unite two words or sentences so that the meaning or intention conveyed is easily understood. This research aims to identify and classify the forms of coordinative conjunctions in detail. The data sources in this research are educational and educational articles on the website kelasjuara.id. Two methods are used in this research, namely, the descriptive qualitative method and the theoretical approach in syntax. The data collection used in this research is listening and noting. In analyzing the data, the method used is agih method. The data presentation technique is a formal technique in the form of a table and an informal technique in the form of narration. Based on the analysis, the most common coordinative conjunction found in the article is the addition coordinative conjunction with 127 conjunctions. The one not found in the article is the ordering coordinative conjunction. Selection coordinative conjunction is 16 conjunctions, opposition coordinative conjunction is 4 conjunctions, correction, affirmation, restriction coordinative conjunction is 2 conjunctions each, equalization coordinative conjunction is 8 conjunctions, and inference coordinative conjunction is 1 conjunction. So, the total number of data is 162 conjunctions. The benefit of this research is to make it easier to understand sentences because conjunctions affect the clarity of meaning in a sentence.